2020
DOI: 10.1038/s41586-020-2926-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemico-genetic discovery of astrocytic control of inhibition in vivo

Abstract: Summary Perisynaptic astrocyte processes are an integral part of central nervous system synapses 1 , 2 ; however, the molecular mechanisms governing astrocyte-synapse adhesions and how astrocyte contacts control synapse formation and function are largely unknown. Here we develop an in vivo chemico-genetic approach, Split-TurboID, that uses a cell surface fragment complementation strategy. We thus identify a proteome enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(167 citation statements)
references
References 50 publications
5
151
0
Order By: Relevance
“…Because these proteins are not known to physically interact, it remains to be seen how Hevin and SPARC function together to tune synapse number in vivo [26]. More recently, a novel in vivo enzymatic assay defined a proteome for extracellular astrocyte-neuron junctions in the primary visual cortex (V1 cortex) and found that astrocytic Neuronal Cell Adhesion Molecule (NRCAM) binds to NRCAM-gephyrin complexes on postsynaptic neurons to induce the formation and function of inhibitory GABAergic synapses, with only minor effects on excitatory synapses [71]. Together, these results identify a direct role for astrocytes in the control of excitatory and inhibitory synapse assembly and maturation in vivo, while also displaying the heterogeneity of astroglial cues depending on the synapse subtype.…”
Section: Astrocytes In Synaptogenesismentioning
confidence: 99%
“…Because these proteins are not known to physically interact, it remains to be seen how Hevin and SPARC function together to tune synapse number in vivo [26]. More recently, a novel in vivo enzymatic assay defined a proteome for extracellular astrocyte-neuron junctions in the primary visual cortex (V1 cortex) and found that astrocytic Neuronal Cell Adhesion Molecule (NRCAM) binds to NRCAM-gephyrin complexes on postsynaptic neurons to induce the formation and function of inhibitory GABAergic synapses, with only minor effects on excitatory synapses [71]. Together, these results identify a direct role for astrocytes in the control of excitatory and inhibitory synapse assembly and maturation in vivo, while also displaying the heterogeneity of astroglial cues depending on the synapse subtype.…”
Section: Astrocytes In Synaptogenesismentioning
confidence: 99%
“…Our recent study on synaptic plasticity is one example (Henneberger et al, 2020), in which results from volume fraction measurements were then further investigated using STED and electron microscopy. Other options are techniques for locating neuron-astrocyte interaction sites using proximity assays (Octeau et al, 2018) and for identifying the proteins enriched at such contact sites (Takano et al, 2020).…”
Section: Capturing Heterogeneity and Developmental Changes Of Astrocyte Morphologymentioning
confidence: 99%
“…In particular, astrocytes promote synapse formation through the secretion of synaptogenic factors (e.g. SPARCL1, thrombospondins, ApoE, Chordin-like 1, TGF, and glypicans) [7][8][9][10][11][12] and via contactdependent mechanisms [13][14][15] . However, the role of astrocytes in synaptogenesis and synaptic pruning does not readily explain why they make persistent intercellular junctions with synapses well after their formation and into adulthood.…”
mentioning
confidence: 99%